Parental involvement and health risk behaviors among Lebanese high school students - Issa, Marie-Anne Salah (Beirut American University of Beirut - Faculty of Arts and Sciences - Department of Education, 2007)
The current study investigated the relationship between health risk behaviors an d parental involvement among Lebanese high school students, in addition to the r ole of some socio-demographic variables such as gender, economic status, parenta l education, family size and structure, and religiosity. The sample included 283 students from English-speaking private high schools in B eirut. The survey contained three measures: the Youth Risk Behavior Survey (YRBS ; CDC, 2005), the Authoritative Parenting Measure (Lamborn et al., 1991), and a Religiosity Scale (Harb, n.d.). The findings showed that gender and religiosity were the most prominent predicto rs of health risk behaviors in general. The father's level of education was a si gnificant predictor of drug and alcohol use. Parental involvement, the family si ze and structure, and the economic status did not emerge as significant predicto rs. The findings were then discussed, limitations were identified, and future di rections were suggested.
: Mémoire
Keywords: Cycle Secondaire; Education Sanitaire; Etablissement scolaire et parents; Health education; School and Parents; Secondary Education